2010
DOI: 10.1021/pr9012078
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Reference Map and Comparative Proteomic Analysis between a Wild TypeClostridium acetobutylicumDSM 1731 and its Mutant with Enhanced Butanol Tolerance and Butanol Yield

Abstract: The solventogenic bacterium Clostridium acetobutylicum is an important species of the Clostridium community. To develop a fundamental tool that is useful for biological studies of C. acetobutylicum, we established a high resolution proteome reference map for this species. We identified 1206 spots representing 564 different proteins by mass spectrometry, covering approximately 50% of major metabolic pathways. To better understand the relationship between butanol tolerance and butanol yield, we performed a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 70 publications
3
100
0
1
Order By: Relevance
“…In addition, it facilitates the first step in the formation of acetone (Andersch et al 1983;. This view is supported by several experimental studies which had observed an increased transcription of the encoding genes, ctfA and ctfB, which are part of the sol operon (Grimmler et al 2011;Jones et al 2008), and an increased intracellular concentration of the protein during the pH-induced shift and during solventogenesis (Janssen et al 2010;Mao et al 2010). However, recent experimental evidence indicates that an alternative re-assimilation mechanism for butyrate could exist which is independent of the CoA-transferase (Desai et al 1999;Lehmann et al 2012a) and may rely on a pH-dependent reverse activity of the butyrate forming enzymes (Desai et al 1999;Lehmann et al 2012b).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, it facilitates the first step in the formation of acetone (Andersch et al 1983;. This view is supported by several experimental studies which had observed an increased transcription of the encoding genes, ctfA and ctfB, which are part of the sol operon (Grimmler et al 2011;Jones et al 2008), and an increased intracellular concentration of the protein during the pH-induced shift and during solventogenesis (Janssen et al 2010;Mao et al 2010). However, recent experimental evidence indicates that an alternative re-assimilation mechanism for butyrate could exist which is independent of the CoA-transferase (Desai et al 1999;Lehmann et al 2012a) and may rely on a pH-dependent reverse activity of the butyrate forming enzymes (Desai et al 1999;Lehmann et al 2012b).…”
Section: Introductionmentioning
confidence: 70%
“…During exponential growth acetate and butyrate are produced (acidogenic phase). This type of anaerobic metabolism enables the organism to gain the maximal amount of energy (ATP) per mole glucose using substrate-level phosphorylation (Madigan et al 2009). During the transition to the stationary phase the metabolism switches to the formation primarily of acetone and butanol (solventogenic phase).…”
Section: Introductionmentioning
confidence: 99%
“…The gel was stained with Coomassie Blue after electrophoresis. The putative recombinant protein in the SDS-PAGE gel was cut out, and then matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis was performed as described by Mao et al 31) For protein purification, the selected transformant and the transformant with an empty vector were fermented under the same culture conditions. The proteins in the supernatant fluid, the volume of which was normalized according to the OD600 value, were precipitated with 50% ammonium sulphate overnight.…”
Section: Methodsmentioning
confidence: 99%
“…We applied a similar procedure to engineering n-butanol tolerance -E. coli cells carrying pQ-lib were serially transferred in media containing gradually increased n-butanol concentrations. Considering that improvement of complex traits such as n-butanol tolerance might require accumulation of much more adaptive mutations [31,32], the pQ-lib carrying cells were transferred in each n-butanol concentrations for three times, upon full growth, before transferring to the next higher butanol concentration. Figure 4A showed that pQ-lib carrying cells exhibited a better adaptability to the increased n-butanol concentrations.…”
Section: Greace Can Be Successfully Applied To Engineer N-butanol Andmentioning
confidence: 99%